Respuesta :

Answer in a different form or solutions?

Answer:

x = 5/2 and x = -1/3

Step-by-step explanation:

[tex]6x^{2} - 13x - 5\\=x^{2} - \frac{13x}{6} - \frac{5}{6}\\=(x^2 - 2*x*\frac{13}{12} + \frac{169}{144}) - \frac{289}{144} \\So: (x - \frac{13}{12} )^2 = \frac{289}{144} \\ \\First situation: x -\frac{13}{12} = \sqrt{\frac{289}{144} } = \frac{17}{12} \\So : x = \frac{17}{12} + \frac{13}{12} = \frac{5}{2} \\\\Second situation: x - 13/12 = -\sqrt{\frac{289}{144} } = -\frac{17}{12} \\So : x = -\frac{17}{12} + \frac{13}{12} = \frac{-1}{3} \\\\In conclusion, x =\frac{5}{2} and x = \frac{-1}{3} \\[/tex]Brainliest? It costs me about 20 min :(